A representação cultural gauchesca do município de Passo Fundo - Ribas, João Vicente (2008)
The subject of this study is the representation of Passo Fundo city through its gauchesca identity (term regarding the South-Brazilian Gaúcho, from Rio Grande do Sul, (Portuguese speaking). The research includes agents and spaces engaged in the invention and reproduction of this identity in the town, in the cultural, political and media scopes, as a way of representation of the municipality. History books, events, media coverage and political projects that deal with this issue are assessed, since the foundation of the first Gaucho s Tradition Centre, in 1952, through the recording of the Gaúcho de Passo Fundo film, by Teixeirinha, up to the celebrations of the 150th anniversary about the political emancipation of the town, in 2007